Current Treatment Options in Vestibular Migraine - Obermann, Mark; Strupp, Michael (Frontiers in Neurology, 2014)
Approximately 1% of the general population in western industrialized countries suffers from vestibular migraine. However, it remains widely unknown and often under diagnosed even despite the recently published diagnostic criteria for vestibular migraine. Treatment trials that specialize on vestibular migraine are scarce and systematic randomized controlled clinical trials are only now emerging. This review summarizes the knowledge on the currently available treatment options that were tested specifically for vestibular migraine and gives an evidence-based, informed treatment recommendation with all its limitations. To date only two randomized controlled treatment trials provide limited evidence for the use of rizatriptan and zolmitriptan for the treatment of vestibular migraine attacks because of methodological shortcommings. There is an on-going a multicenter randomized placebo-controlled trial testing metoprolol 95 mg vs. placebo (PROVEMIG-trial). Therefore, the therapeutic recommendations for the prophylactic treatment of vestibular migraine are currently widely based on the guidelines of migraine with and without aura as well as expert opinion.